Spaces of Racialization: Ireland's Direct Provision Asylum Centres as Sites of Racialized State Violence. (18th June 2022) - Lentin, Ronit
Abstract : Since November 1999, people arriving in Ireland to seek asylum have been dispersed throughout the country and confined in Direct Provision (DP) accommodation centres. Though initially meant for a six-month stay, by May 2020 7, 700 people were living in 85 DP and emergency accommodation centres, many of them for up to nine years. The centres are operated by for-profit private companies who have been paid 1.6 billion euros since 2000, and are mostly sited in remote locations outside cities, on the periphery of society. The confinement of asylum seekers has been disavowed by state and society and continues the disavowal by Irish state and society of the coercive confinement of unwed mothers and poor children in church-run institutions, where women and children were confined and enslaved until late in the twentieth century. This article is based on interviews with and publicly available testimonies of asylum seekers in Direct Provision and on public and social media statements by the Movement of Asylum Seekers in Ireland (MASI). It theorizes the DP centres as racialized zones of nonbeing (Fanon 1967: 8) and the DP regime as racialized state violence. The segregation and racialization of asylum seekers in Direct Provision were poignantly demonstrated by asylum seekers' inability to observe social distancing in overcrowded DP centres during the early days of the Covid-19 pandemic, leading to a considerable number of them being infected.